Methane steam reforming catalyst as well as preparation method and application thereof
By introducing nickel on cerium-zirconium-aluminum composite oxide and introducing lanthanum using urea deposition method, an efficient nickel-lanthanum doping catalyst was prepared, which solved the problem of existing catalysts resisting carbon deposits and activity loss in the SOFC system, and achieved high efficiency The methane conversion rate and stable battery power generation performance are suitable for low temperature and low cost SOFC system applications.
Patent Information
- Application Number
- CN202411339599.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
When used in combination with the SOFC system, existing methane water vapor reforming catalysts have problems such as poor carbon deposit resistance and loss of active components, resulting in a decline in battery power generation performance and high cost of precious metal catalysts. Non-precious metal catalysts such as nickel-based catalysts are also faced. Problems of carbon deposits and sintering inactivation.
By impregnating cerium-zirconium-aluminum composite oxides into nickel and introducing lanthanum using urea deposition method, a nickel-doped cerium-zirconium-aluminum composite oxide catalyst is prepared to improve the dispersion and catalytic activity of nickel, suitable for 400-550℃ Methane reforming temperature range to achieve efficient methane conversion.
The catalyst achieves a methane conversion rate of more than 45% in the temperature range of 400-550°C, which improves the power generation performance of the battery and the stability of the catalyst, reduces costs, and is suitable for the low-temperature and low-cost catalyst requirements of SOFC systems.
Smart Images

Figure CN119259059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a methane steam reforming catalyst and a preparation method and application thereof. The catalyst is suitable for methane steam reforming coupled with a SOFC system. Background Art
[0002] With the decline of crude oil resources and the emergence of environmental problems, people are paying more and more attention to finding and focusing on the development of alternative energy sources and diversifying energy sources. Solid oxide fuel cells (SOFCs) are a new type of power generation method that can achieve unidirectional conversion of chemical energy into electrical energy and meet the various requirements of modern power generation technology for environmental sustainable development. Considering the actual development of SOFC, the readily available methane can be used to convert it into synthesis gas (containing a certain proportion of hydrogen and carbon monoxide), namely the methane steam reforming reaction. The reaction equation is as follows: CH4 + H2O = CO + 3H2 = 206.3 kJ·mol -1 .
[0003] The product is then introduced into SOFC as gas fuel for power generation, which takes advantage of methane's easy availability and safe storage and transportation, and fully utilizes hydrogen's high calorific value, high power generation efficiency, low carbon deposition, and pollution-free product characteristics.
[0004] In the process of methane steam reforming, catalysts play an important role. Ni-based catalysts have poor anti-carbon deposition performance and also have problems such as mismatch when used in conjunction with SOFC systems. Therefore, it is necessary to study methane steam reforming catalysts and prepare efficient anti-carbon deposition catalysts suitable for use in SOFC system reforming devices.
[0005] At present, there are many types of methane reforming catalysts, including supported catalysts, spinel catalysts, perovskite catalysts, mesoporous catalysts, etc. Among them, supported catalysts are more common. However, no matter what type of catalyst it is, its active components must have the ability to dissociate methane molecules and activate HO and CH bonds during the catalytic process. The focus of research on the active components of catalysts is mainly on two categories: precious metals and non-precious metals. Precious metal catalysts such as Pt, Pd, Rh, Ir, etc., generally have an activity order of Rh>Pt>Pd>Ir. Among them, Rh and Pt have attracted the attention of foreign researchers for their excellent reaction activity and anti-carbon deposition performance. However, their high cost still makes it difficult to apply them to industrial production on a large scale. Similarly, people have been studying non-precious metal catalysts, hoping to find a cheap catalyst that can replace precious metals. Ni, Co and Fe are the main active components of non-precious metal catalysts, and their activity order is generally: Ni>Co>Fe. People have conducted extensive and in-depth research on nickel-based catalysts and found that nickel-based catalysts have comparable activity to precious metal catalysts, and are cheap and have good application prospects. Nickel-based catalysts also face the problem of deactivation due to carbon deposition, sintering and loss of active components.
[0006] The coupling of SOFC and fuel reforming, the reforming device reforms the fuel gas, and then the reformed gas enters the fuel cell to generate electricity. The two parts work independently, and the entire coupling process is modular. When the fuel gas is pure H2, the battery shows the best discharge performance. When the fuel gas is reformed tail gas, the battery discharge performance is slightly attenuated, which may be because there is a certain amount of CO in its components, which will produce certain carbon deposits compared with pure hydrogen, affecting the electrochemical performance. The battery has poor discharge performance when using pure methane as fuel gas. The use of methane affects the catalytic performance of the battery anode and greatly reduces the power density of the battery. In the comparison of the discharge performance of the battery with reformed gas as gas fuel, it can be seen that after methane is reformed and introduced into the SOFC system, it can greatly improve the power generation capacity of the battery and increase the maximum power density of the single cell discharge. Therefore, the tail gas generated by the methane-steam reforming device can meet the requirements of SOFC for fuel gas, and has the feasibility of being used as the fuel gas of the SOFC system. The methane steam reforming device and the SOFC system can be smoothly connected for coupling application, and the waste heat can be reused while generating electricity, so as to improve the comprehensive utilization rate of energy and achieve the goal of high efficiency and environmental protection. Summary of the invention
[0007] The purpose of the present invention is to provide a methane steam reforming catalyst and a preparation method thereof. The catalyst of the present invention is suitable for methane steam reforming coupled with a SOFC system and can be used in a SOFC power generation system.
[0008] The preparation method of the present invention comprises: (A) immersing a cerium-zirconium-aluminum composite oxide in an aqueous solution of a soluble nickel salt to introduce nickel into the cerium-zirconium-aluminum composite oxide, thereby obtaining a cerium-zirconium-aluminum composite oxide into which nickel has been introduced; (B) using a soluble lanthanum salt, by urea precipitation method, lanthanum is introduced into the cerium-zirconium-aluminum composite oxide introduced with nickel obtained in step (1), thereby obtaining a cerium-zirconium-aluminum composite oxide introduced with nickel and lanthanum; (C) The cerium-zirconium-aluminum composite oxide into which nickel and lanthanum are introduced is dried.
[0009] Preferably, in step (A), the amount of soluble nickel salt is such that nickel element accounts for 0.5-20wt% of the cerium-zirconium-aluminum composite oxide, preferably 0.6-15wt%, preferably 0.8-12wt%, and more preferably 1wt%~10wt%, such as 1.2wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt%. The concentration of the aqueous solution of soluble nickel salt can be, for example, 1-10wt%.
[0010] Preferably, in step (B), the amount of soluble lanthanum salt used is such that the lanthanum element accounts for 8-25wt% of the cerium-zirconium-aluminum composite oxide, preferably 10%-20wt%, for example 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%.
[0011] Preferably, step (B) comprises: dispersing the cerium-zirconium-aluminum composite oxide into which nickel is introduced in water, adding a soluble lanthanum salt and urea, stirring at 70-100°C, preferably 80-95°C for more than 2 hours, preferably 3-5 hours, cooling and washing to neutrality, and then drying. After drying, it can be further crushed, for example, ground to a particle size of 10-200 mesh, preferably 40-80 mesh. More preferably, the amount of urea used in the urea precipitation method is 10-1000 times, preferably 50-800 times, and further preferably 100~500 times, further 200-400 times, for example 300 times, of the total molar number of nickel and lanthanum cations in the entire system.
[0012] Preferably, in step (C), drying is carried out at 300-450°C, further at 350-420°C, preferably at about 400°C for more than 1 hour, for example 1-5 hours, preferably about 3 hours. The catalyst is subjected to reduction treatment before use, and can be pre-reduced at 400-500°C in a hydrogen atmosphere for more than 1 hour, for example 1-5 hours, for example, pre-reduced at 450°C in a 10% H2 / Ar atmosphere for 3 hours.
[0013] The soluble nickel salt may be selected from one or more of nickel acetate, nickel chloride, nickel nitrate and nickel sulfate, preferably nickel nitrate hexahydrate.
[0014] The soluble lanthanum salt can be selected from, for example, one or more of lanthanum nitrate, lanthanum carbonate, and the like.
[0015] Preferably, the cerium-zirconium-aluminum composite oxide is prepared by the following steps: Al2O3 as a precursor and cerium-zirconium powder (Zr2Ce3O 10 ) are mixed by a ball mill, and calcined in an air atmosphere to obtain a cerium-zirconium-aluminum composite oxide. Preferably, the mass ratio of aluminum oxide to cerium-zirconium powder is 1:0.5-1:5, such as 1:1, 1:2, 1:3, 1:4, and preferably 1:1, 1:2, 1:3. The aluminum oxide raw material can be commercially available aluminum oxide, and the particle size can be less than 1 micron. The cerium-zirconium powder raw material (cerium-zirconium composite oxide) can be commercially available materials or cerium-zirconium powder prepared according to a known method. The particle size of the prepared cerium-zirconium-aluminum composite oxide is ground to 10-200 mesh, preferably 40 to 80 mesh. In the cerium-zirconium powder raw material, the zirconium-cerium molar ratio can be, for example, 1:0.5~2, such as 1:1.5.
[0016] The nickel and lanthanum in the finished catalyst exist in the form of oxides. Preferably, the nickel element accounts for 1-5wt% of the finished catalyst, and the lanthanum element accounts for 5-10wt% of the finished catalyst.
[0017] In one embodiment, step (A) comprises: Al2O3 (3-5 parts by weight) as a precursor and cerium zirconium powder (Zr2Ce3O 10 , 3-5 parts by weight) are mixed by a ball mill, and calcined in an air atmosphere to obtain a cerium-zirconium-aluminum composite oxide as a carrier, which is recorded as CZA. 1%-5% mass fraction of Ni is loaded, and Ni(NO3)2·6H2O is weighed according to the calculated value and dissolved in deionized water, and then impregnated on the CZA carrier, and then allowed to stand at room temperature for 10-20 hours, for example, 12 hours, and then dried in air at 100-150°C, for example, 110°C for 5-20 hours, for example, 12 hours, and then heated to 450-550°C, preferably about 500°C, at a rate of 5-15°C / min, preferably about 10°C / min in an air atmosphere and calcined for 2-10 hours, preferably about 4 hours. The obtained sample is recorded as Ni-CZA.
[0018] In one embodiment, step (B) comprises: 5%-10% La is introduced into the cerium-zirconium-aluminum composite oxide by a urea precipitation method. Ni-CZA is taken as a carrier and distilled water is added to a container. The amount of water is 100-500 times that of Ni-CZA. Ultrasonic dispersion is performed (for example, for 10-60 minutes). La(NO3)3·6H2O and urea in an amount of 200 times the total molar amount of cations (total molar amount of nickel and lanthanum) are then added respectively. The mixture is stirred at 80-120°C (preferably 90-95°C) for 1-10h, for example, at 90°C for 4h. After the solution is cooled, the mixture is washed to neutrality, for example, thoroughly washed to neutrality with water and ethanol, placed in a drying oven for drying, ground (ground to a particle size of 40 to 80 meshes) for standby use, and recorded as Ni5-La. 10 -CZA. In the finished catalyst, nickel and lanthanum are present in the form of oxides.
[0019] The present invention further provides a catalyst obtained by the above preparation method.
[0020] The present invention also provides use of the catalyst for low-temperature reforming of methane with water vapor.
[0021] In the present application, "optionally" means with or without.
[0022] Advantages of the present invention: 1. The active component Ni is introduced on a specific carrier of cerium-zirconium-aluminum composite oxide, and the rare earth element La is introduced by urea deposition method. The rare earth element improves the dispersion of the active component Ni. The urea deposition method has a faster crystallization speed, which makes the elements more evenly loaded on the carrier, thereby improving the performance of the catalyst. 2. The catalyst of the present invention can achieve a methane conversion rate of more than 45%, especially more than 50%, in the methane reforming temperature range of 400-550°C. By adjusting the La loading and Ni loading, the CH4 conversion rate is greater than 45.0% under certain conditions, and the methane conversion rate is precisely adjusted to change the gas ratio on the anode side of the battery to meet the optimal power generation temperature range of the battery design. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 To show the Ni5-La prepared in Example 1 10 -HAADF-STEM image and EDS spectrum of element distribution on the surface of CZA catalyst, the upper left is Ni5-La 10 -HAADF-STEM image of CZA catalyst, the upper right, lower left and lower right are EDS surface scans representing the elements O, Ni and La respectively.
[0024] Figure 2 The effect of different temperatures on steam reforming of methane is shown.
[0025] Figure 3Schematic diagram of the coupling between steam reforming and SOFC system.
[0026] Figure 4 (a) is a diagram of module voltage and current when the reforming catalyst of the present invention is actually applied to a SOFC system to generate electricity for 1800 hours; (b) is a diagram of module output power. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The methane steam low temperature reforming catalyst and the preparation method thereof provided by the embodiments of the present invention are described in detail below with reference to the accompanying drawings. Example 1
[0029] Preparation of Ni-CZA catalyst Al2O3 (5 g) as a precursor and cerium zirconium powder Zr2Ce3O 10 (5g) were mixed by ball mill and calcined in air atmosphere to obtain cerium zirconium aluminum composite oxide as a carrier. The molar ratio of zirconium: cerium: aluminum in cerium zirconium aluminum composite oxide was 2: 3: 15. It was recorded as CZA, and 5wt% Ni (in terms of nickel element) was loaded. According to the calculated value, Ni(NO3)2·6H2O was weighed and dissolved in deionized water and then impregnated on the CZA carrier. Then, it was allowed to stand at room temperature for 12 h, and then dried in air at 110℃ for 12 h. Then, it was heated to 500℃ at a rate of 10℃ / min in air atmosphere and calcined for 4 h. The obtained sample was recorded as Ni5-CZA.
[0030] Ni5-La 10 - Preparation of CZA catalyst 10wt% La (calculated as lanthanum element) was introduced into the cerium zirconium aluminum composite oxide by urea precipitation method. 500mg Ni5-CZA was taken as a carrier and added to 100 mL of distilled water in a 250 mL three-necked flask, and ultrasonic dispersion was performed for 30 minutes. Then, 10wt% La(NO3)3·6H2O of the weight of the cerium zirconium aluminum composite oxide and 200 times the total molar amount of urea of nickel lanthanum cations were added, and stirred at 90 °C for 4 h. After the solution was cooled, it was thoroughly washed with water and ethanol to neutrality, placed in a drying oven for drying, ground and used for later use, and recorded as Ni5-La 10 -CZA. In the finished catalyst, nickel and lanthanum are present in the form of oxides.
[0031] Catalyst characterization results The prepared Ni5-La 10 -CZA catalyst surface element distribution was characterized, and the results are as follows Figure 1 As shown in the figure, the pixels of corresponding colors show that La and Ni exist on the catalyst surface. The distribution of pixels also shows that Ni is evenly distributed on the catalyst surface. The urea deposition method was used to successfully prepare Ni5-La with evenly distributed active components. 10 -CZA and other catalysts, a uniformly dispersed catalyst is beneficial to improving its catalytic activity.
[0032] The carrier and the prepared Ni5-La were tested by BET tester. 10 -CZA and other catalyst pore structures were characterized to analyze the changes in specific surface area and pore size before and after catalyst preparation. The specific surface area and pore size distribution before and after are shown in Table 1.
[0033] Table 1 Specific surface area, pore volume and pore diameter of different catalysts
[0034] From the data in the table above, it can be found that the specific surface area of the carrier Ni5-CZA before preparation is 123.49 m 2 ·g -1 , the average pore size is 10.1nm, while the specific surface area and average pore size of the catalyst prepared by urea precipitation method are reduced to varying degrees, such as Ni5-La 10 -The specific surface area of CZA catalyst was reduced to 119.28 m 2 ·g -1 , the average pore size is reduced to 8.82 nm. It is speculated that the reason for the reduction in specific surface area and average pore size may be that during the impregnation and calcination process, the active components exist in the form of NiAl2O4 and NiO on the catalyst surface and in the internal pores, occupying a certain pore space. In addition, during the calcination process, Ni interacts with Al2O3 to form nickel aluminum spinel NiAl2O4. The grains formed under high temperature will grow and agglomerate, which also reduces the specific surface area of the catalyst to a certain extent. However, despite this, the specific surface area and average pore size of the catalyst are still maintained at a relatively high level in terms of value. A higher specific surface area can provide more platforms for the attachment of active Ni particles to make them more evenly dispersed, thereby ensuring that the catalyst has a higher catalytic activity. Example 2
[0035] The same as Example 1, except that the amount of nickel salt used is 3wt% and the amount of lanthanum salt used is 16wt%. Example 3
[0036] The same as Example 1, except that the amount of nickel salt used is 7wt% and the amount of lanthanum salt used is 12wt%.
[0037] Test Example 1 Evaluation of Catalyst Performance under Different Space Velocity Conditions The catalyst prepared as described in Example 1 was used at 550°C, pressure 1.0 MPa, water-carbon ratio 2:1, carbon space velocity 500-3000h -1 The airspeed condition investigation experiment was carried out under the conditions shown in Table 2. -1 , the conversion rate of methane is relatively high, the hydrogen content is about 55.6%, the CO content is about 9.4%, and the CO2 content is 7.6%. This indicates that at a volume space velocity of 1000 h -1 When methane is reformed, the composition of the gas synthesized is relatively stable.
[0038] Table 2 Comparison of catalyst performance under different space velocity conditions
[0039] Conversion rate calculation formula: X(CH4)=1-ƒ(CH4) / [ƒ(CH4)+ƒ(CO)+ ƒ(CO2)] where ƒ is the volume or mole fraction of each gas in the reaction product.
[0040] Comparison of the catalyst performance of the catalyst of the present invention with that of the existing catalyst
[0041] 15%Ni-ZrO2 is a catalyst with a nickel loading of 15% prepared by impregnation method, and the carrier is zirconium oxide.
[0042] 15%Ni-Ce 0.2 O 0.8 The nickel catalyst with a loading of 15% was prepared by impregnation method, and the support was Ce 0.2 O 0.8 .
[0043] Ni5-La 10 -CZA is a nickel-lanthanum catalyst prepared by impregnation method.
[0044] Ni5-La 10 -CZA is the catalyst prepared by the present invention.
[0045] It can be seen from the above table that the CH4 conversion rate of the catalyst of the present invention is significantly higher than that of other catalysts.
[0046] At present, in order to obtain a higher methane conversion rate, the reaction temperature of the methane reforming catalyst in the industry is generally set at 750-920°C, which can achieve a conversion rate of more than 90%. However, the methane reforming temperature range suitable for the SOFC system is 400-550°C. The CH4 conversion rate of the catalyst of the present invention in this temperature range is 50%. Therefore, the catalyst of the present invention is a low-temperature and low-cost catalyst suitable for SOFC requirements.
[0047] Test Example 2 Evaluation of catalyst performance under different temperature conditions The catalyst performance test was carried out in a fixed bed reactor. Before the test, the catalyst was reduced with hydrogen at a flow rate of 100 mL / min and a reduction temperature of 700°C. After 2 h of reduction, the fixed bed reactor was naturally cooled under nitrogen protection. After the fixed bed temperature was cooled to 100°C, the catalyst activity was tested at different temperatures. The test conditions were: volume space velocity of 1000 h -1 , the water-to-carbon ratio (molar ratio of water vapor to methane) is 2, and the reaction pressure is 101.325 kPa. The reaction results are as follows Figure 2 As shown. Figure 2 It can be seen that at 300°C, the catalyst activity is relatively low and the H2 content in the synthesis gas is slightly low; as the reaction temperature increases, the methane conversion rate increases rapidly, and the catalyst activity increases with the increase in temperature. When the temperature is 550°C, the methane conversion rate reaches 50%. Before 450°C, the H2 content in the synthesis gas increases with the increase in temperature. When the temperature is greater than 450°C, the H2 content gradually stabilizes with the increase in temperature. The CO content increases with the increase in temperature. The mechanism of the change of gas composition in the synthesis gas with temperature is relatively complex, which is related to the reaction state of the steam reforming reaction and side reactions (such as water-gas shift reaction, cracking reaction, etc.).
[0048] Experimental Example 3: Coupling of Steam Reforming and SOFC System In order to facilitate the performance evaluation of the methane steam reforming catalyst and the operation of the SOFC power generation system, the steam reforming and SOFC system coupling will adopt an external reforming method, that is, the tail gas generated by the methane steam reforming reaction is all introduced into the fuel cell to generate electricity. At the same time, we also found that the SOFC system generally works at high temperature, and a large amount of waste heat is generated while using the reformed gas to generate electricity. If this part of the waste heat can be well utilized, it will be able to greatly improve the comprehensive utilization rate of energy and save the consumption of other fossil fuels. Therefore, in order to further improve the energy integration of the coupled application of the steam reforming device and the SOFC system, the present invention proposes to design a combined heat and power scheme, which can not only couple the two to generate electricity, but also use the generated waste heat for secondary utilization to improve the comprehensive utilization rate of energy.
[0049] like Figure 3As shown, natural gas and water vapor enter the preheating device for component preheating, and then enter the reforming device for water vapor reforming. The H2, CO obtained by reforming and the remaining CH4 and water vapor are introduced into the SOFC system together to generate electricity, and the generated electricity can be used for household use; and a part of the unreacted gas remaining from power generation will be introduced into the burner as fuel for combustion, and the heat of combustion will provide heat for the whole composed of the preheating device, the reforming device and the SOFC system to meet the working temperature of different systems. The exhaust gas generated by the burner combustion also has a very high temperature. The present invention is also designed to make full use of this part of the heat, and exchange heat between household cold water and combustion exhaust gas to turn cold water into hot water for household use; the final condensed water can be recycled and used, the exhaust gas is discharged or collected for standby, and the system continues to work in a cycle.
[0050] By testing the performance of methane steam reforming catalyst under different reaction conditions, the optimal catalytic reforming conditions for methane steam coupled SOFC stack external reforming were determined. Under the optimal catalytic reforming conditions, methane steam reforming and SOFC stack coupling power generation were achieved. The test found that when the methane fuel flow rate was 200 L / min, the power of the stack was slightly lower than the power measured with hydrogen as fuel. Under continuous constant current load, the electrochemical performance of the SOFC stack was relatively stable for more than 1800 hours of continuous testing, without obvious attenuation, and the stack voltage and stack power remained basically stable. Figure 4 shown. Figure 4 This is the experimental data of the actual application of reforming catalyst in the SOFC system to generate electricity for 1800 hours in 2023.
[0051] Finally, it should be noted that the above content is only for illustrative purposes and not for limiting the scope of protection of the present invention. A person skilled in the art may modify or substitute equivalents for the technical solution of the present invention without departing from the essence of the present invention, and the modifications or equivalent substitutions shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a methane steam reforming catalyst, comprising: (A) immersing a cerium-zirconium-aluminum composite oxide in an aqueous solution of a soluble nickel salt to introduce nickel into the cerium-zirconium-aluminum composite oxide, thereby obtaining a cerium-zirconium-aluminum composite oxide into which nickel has been introduced; (B) using a soluble lanthanum salt, by urea precipitation method, lanthanum is introduced into the cerium-zirconium-aluminum composite oxide introduced with nickel obtained in step (1), thereby obtaining a cerium-zirconium-aluminum composite oxide introduced with nickel and lanthanum; (C) The cerium-zirconium-aluminum composite oxide into which nickel and lanthanum are introduced is dried.
2. The preparation method according to claim 1, characterized in that: In step (A), the nickel element accounts for 0.5-20 wt %, preferably 0.8-12 wt %, and more preferably 1 wt % to 10 wt % of the cerium-zirconium-aluminum composite oxide.
3. The preparation method according to claim 2, characterized in that: The lanthanum element accounts for 8-25 wt % of the cerium-zirconium-aluminum composite oxide, preferably 10-20 wt %.
4. The preparation method according to any one of claims 1 to 3, characterized in that Step (B) comprises: dispersing the cerium-zirconium-aluminum composite oxide introduced with nickel in water, adding soluble lanthanum salt and urea, stirring for 3-5 hours under heating at 80-95°C, cooling and washing to neutrality, and then drying, and optionally further pulverizing after drying.
5. The preparation method according to claim 4, characterized in that: The amount of urea used in the urea precipitation method is 10-1000 times, preferably 50-800 times, and more preferably 100-500 times the total molar number of nickel and lanthanum cations in the entire system.
6. The preparation method according to any one of claims 1 to 3, characterized in that: In step (C), drying is carried out at 300-450°C, preferably at about 400°C for 1-5 hours, preferably about 3 hours. The catalyst is subjected to reduction treatment before use, and is pre-reduced at 400-500°C in a hydrogen atmosphere for 1-5 hours, for example, at 450°C in a 10% H2 / Ar atmosphere for 3 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that The soluble nickel salt is selected from one or more of nickel acetate, nickel chloride, nickel nitrate and nickel sulfate, preferably nickel nitrate hexahydrate; the soluble lanthanum salt is selected from one or both of lanthanum nitrate and lanthanum carbonate.
8. The preparation method according to any one of claims 1 to 7, characterized in that: Cerium-zirconium-aluminum composite oxide is prepared by the following steps: Al2O3 is used as a precursor and cerium-zirconium powder (Zr2Ce3O 10 ) are mixed by a ball mill, and calcined in an air atmosphere to obtain a cerium-zirconium-aluminum composite oxide; Preferably, the mass ratio of aluminum oxide to cerium-zirconium powder is 1:1, 1:2, 1:3, 1:4 or 1:5, and more preferably 1:1, 1:2 or 1:
3.
9. A methane steam reforming catalyst obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the methane steam reforming catalyst according to claim 9 for low-temperature reforming of methane steam.